La fabrique de repères dans l'alimentation : entre objectivation stratégique de l’organisation de la valeur et euphémisation marchande. Le cas du Franco-Score d’Intermarché - Marie-Lise Buisson (Communiquer)
Shortly after the introduction of the Nutri-Score in France, which evaluates the nutritional quality of food products, the industrial group Intermarché launched the "Franco-Score" to allow consumers to access the proportion of French ingredients contained in food products by displaying it on the packagings. The aim of this article is to examine this particular form of score through the prism of market mediation. Using a cross methodology combining discursive and semiological dimensions, the aim is to understand in what way the implementation of this device proceeds from a strategic objectivation of the organization of value and from a market euphemization which informs us about the market relationship instituted between the brand and the consumer.